2007
DOI: 10.1016/j.cmet.2007.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Increased Internal and External Bacterial Load during Drosophila Aging without Life-Span Trade-Off

Abstract: The role of microbial load during aging of the adult fruit fly Drosophila melanogaster is incompletely understood. Here we show dramatic increases in aerobic and anaerobic bacterial load during aging, both inside the body and on the surface. Scanning electron microscopy and cell staining analyses of the surface of aged flies detected structures resembling abundant small bacteria and bacterial biofilms. Bacteria cultured from laboratory flies included aerobic species Acetobacter aceti, Acetobacter tropicalis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
332
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(379 citation statements)
references
References 51 publications
30
332
5
Order By: Relevance
“…S3D). These findings are consistent with a previous report of increased bacterial loads in aged flies (22) and indicate that loss of intestinal integrity in aged flies is associated with changes in the fly microbiome.…”
supporting
confidence: 93%
“…S3D). These findings are consistent with a previous report of increased bacterial loads in aged flies (22) and indicate that loss of intestinal integrity in aged flies is associated with changes in the fly microbiome.…”
supporting
confidence: 93%
“…Numerous studies have surveyed the gut microbes of Drosophila and identified bacterial communities far less complex than mammals (Corby-Harris et al 2007;Cox and Gilmore 2007;Ren et al 2007;Ryu et al 2008;Chandler et al 2011;Wong et al 2011). An analysis of both laboratory-raised and wild-caught flies found a maximum of 30 operational taxonomic units (OTUs), a proxy for species commonly employed in 16S rRNA gene sequencing analysis, associated with some wild Drosophila, and an average of 6.3 OTUs with laboratory-reared flies (Chandler et al 2011).…”
Section: Fruit Flymentioning
confidence: 99%
“…Gut microbes also play a role in invertebrate biology (Dillon and Dillon, 2003) and digestive process [Brune, 2011 [Lundgren, 2010, and recently the composition of microbe gut populations has been described in a variety of insect species, including bees (Jeyaprakash et al, 2003;Mohr and Tebbe, 2006), beetles (Egert et al, 2005;Lehman et al, 2009;Nardi et al, 2006;Zhang and Jackson, 2008), flies (Cox and Gilmore, 2007;Ren et al, 2007;Ryu et al, 2008;Shin et al, 2011;Wong et al, 2011), lepidopterans (Pauchet et al, 2010;Xiang et al, 2006) and termites (Hongoh et al, 2003). In Drosophila, the microbiome regulates host metabolic homeostatic and developmental programs by modulating the insulin/insulin-like growth factor (Shin et al, 2011).…”
Section: Microbiota: a Key Component Of Nutritional Immunologymentioning
confidence: 99%